Netsuké - Jonas, F. M. (Charles E. Tuttle Company, 1969)
One of the chief attractions of the book is its impressive set of illustrations. these consist of fifty-five photographic plates-nine of them in color - picturing a total of 214 netsuke, ranging from the late 17th to the late 19th century. Also shown are a number of inro, the medicine or seal boxes to which the netsuke were attached to serve as pendants or toggles.